기계경비원의 경비능력이 직무만족에 미치는 영향 - 신재헌; Shin, Jaehun (한국재난정보학회 논문집, 17(3), 2021)
Purpose: The purpose of this study is to examine the influence of electronic security guard's security performance on the job satisfaction and to make proposals on improvement of employment status and job satisfaction. Method: To accomplish the purpose, this study organized the theoretical background by referring to the preceding researches on the related field. Then, this study conducted a survey on electronic security guards and analyzed the results in statistical methods. Result: According to analysis results, electronic security guard's security performances including academic background, martial art skills, height, weight, and BMI index had a significant influence on factors composing the job satisfaction. Conclusion: To improve the electronic security guard's job satisfaction level, this study suggested measures for improving the wage system and reducing turnover rate. This study also suggested measures for strengthening the physical standards and strengthening the practical training for employment. 연구목적: 이 연구는 기계비원의 경비능력이 직무만족에 미치는 영향을 살펴보고 채용실태개선과 직무만족 개선을 제시하기 위한 목적을 가진 연구이다. 연구방법:연구의 목적을 달성하기 위하여 이 연구에서는 관련분야에 대한 선행연구 등을 참조하여 이론적 배경을 구성하였고, 기계경비원에 대한 설문조사를 통하여 얻어진 자료를 통계적기법으로 분석하였다. 연구결과: 분석 결과, 기계경비원의 경비능력인 학력, 무도능력, 근무기간, 신장, 체중, BMI지수는 직무만족을 구성하는 요소들에 유의미한 영향을 끼치는 것으로 나타났다. 결론: 기계경비원들의 직무만족 수준을 강화하기 위하여 보수체계계선과 함께 이직율을 약화시키기 위한 방안 제시 및 채용 시 신체적 기준 강화 및 실무에 맞는 교육 강화 방안을 제안하였다.